Characterizing the role of disparity information in alleviating visual crowding - Astle, Andrew T.; McGovern, David P.; McGraw, Paul V. (Association for Research in Vision and Ophthalmology, 2014)
The ability to identify a target is reduced by the presence of nearby objects, a phenomenon known as visual crowding. The extent to which crowding impairs our perception is generally governed by the degree of similarity between a target stimulus and its surrounding flankers. Here we investigated the influence of disparity differences between target and flankers on crowding. Orientation discrimination thresholds for a parafoveal target were first measured when the target and flankers were presented at the same depth to establish a flanker separation that induced a significant elevation in threshold for each individual. Flankers were subsequently fixed at this spatial separation while the disparity of the flankers relative to the target was altered. For all participants, thresholds showed a systematic decrease as flanker-target disparity increased. The resulting tuning function was asymmetric: Crowding was lower when the target was perceived to be in front of the flankers rather than behind. A series of control experiments confirmed that these effects were driven by disparity, as opposed to other factors such as flanker-target separation in three-dimensional (3-D) space or monocular positional offsets used to create disparity. When flankers were distributed over a range of crossed and uncrossed disparities, such that the mean was in the plane of the target, there was an equivalent or greater release of crowding compared to when all flankers were presented at the maximum disparity of that range. Overall, our results suggest that depth cues can reduce the effects of visual crowding, and that this reduction is unlikely to be caused by grouping of flankers or positional shifts in the monocular image.